Synchronous PIV measurements of a self-powered blood turbine and pump couple for right ventricle support - Ucak, Kagan; Karatas, Faruk; Cetinkaya, Emre; Pekkan, Kerem (NATURE PORTFOLIO, 2024)
A blood turbine-pump system (iATVA), resembling a turbocharger was proposed as a mechanical right-heart assist device without external drive power. In this study, the iATVA system is investigated with particular emphasis on the blood turbine flow dynamics. A time-resolved 2D particle image velocimetry (PIV) set-up equipped with a beam splitter and two high speed cameras, allowed simultaneous recordings from both the turbine and pump impellers at 7 different phased-locked instances. The iATVA prototype is 3D printed using an optically clear resin following our earlier PIV protocols. Results showed that magnetically coupled impellers operated synchronously. As the turbine flow rate increased from 1.6 to 2.4 LPM, the rotational speed and relative inlet flow angle increase from 630 to 900 rpm, and 38 to 55% respectively. At the trailing edges, backflow region spanned 3/5 of the total passage outlet flow, and an extra leakage flow was observed at the leading edge. For this early turbine design, approximately, 75% of the turbine blade passage was not contributing to the impulse operation mode. The maximum non-wall shear rate was similar to 2288 s(-1) near to the inlet exit, which is significantly lower than the commercial blood pumps, encouraging further research and blood experiments of this novel concept. Experimental results will improve the hydrodynamic design of the turbine impeller and volute regions and will be useful in computational fluid dynamics validation studies of similar passive devices.
Keywords: Blood turbine; Blood pump; PIV; Ventricular assist device; RVAD; VAD; Right ventricular; Right heart failure; IATVA; Science & Technology - Other Topics